Fourth Five Year Plan - Resources, Outlays and Programmes - Planning Commission (Planning Commission, Government of India, 1965)
The Fourth Five-Year Plan, formulated by the Planning Commission and guided by the priorities of the National Development Council, articulated a comprehensive development strategy aimed at accelerating economic growth while strengthening social services and institutional capacity in India. With a proposed outlay of Rs. 21,500 crores divided between public and private sectors, the Plan emphasized prudent resource mobilization through enhanced taxation, fiscal discipline, and foreign assistance to avoid inflationary financing. A central objective was achieving a 5 percent annual growth rate in agriculture, supported by substantial investments in irrigation, high-yielding varieties, and rural infrastructure, alongside major allocations for power generation, transport expansion, and the promotion of village and small industries to foster balanced regional development. Equally significant was the Plan’s transformative approach to education, which shifted focus from mere expansion to consolidation, quality improvement, and alignment with economic needs through diversification into technical, vocational, commercial, and agricultural streams. Substantial funding was earmarked for elementary, secondary, university, technical, and adult education, with special initiatives for girls’ education, teacher training, scholarships, research, and the integration of educational technology. Health services, family planning, and drinking water supply were also prioritized to enhance human capital and social welfare. By linking agricultural modernization, industrial decentralization, infrastructure growth, and educational reform within a disciplined financial framework, the Fourth Plan sought to strengthen productivity, reduce unemployment and illiteracy, and lay a resilient foundation for sustained economic progress during a critical phase of India’s development trajectory.
Twenty-Second Meeting of the National Development Council
Keywords: Fourth Five-Year Plan; Planning Commission; National Development Council; Agricultural Growth Target; Resource Mobilization; Irrigation Expansion; Power Development; Village and Small Industries; Transport Infrastructure; Educational Reform; Technical and Vocational Education; Adult Literacy